Multi-omics approach reveals CCND1, GABPA, HIF1A, and SOX6 as key regulators and prognostic markers in heart failure - Ping He; Lang Deng; Kaijie Wu (Hereditas)
Abstract Introduction Heart failure (HF) is a progressive condition with complex molecular mechanisms. This study aims to identify potential biomarkers and therapeutic targets by analyzing differentially expressed genes (DEGs) in HF patients, exploring the roles of hub genes, and developing a risk model for predicting disease progression. Methodology We cultured five human HF cell lines and five normal coronary cardiomyocyte cell lines. Gene expression datasets were retrieved from the Gene Expression Omnibus (GEO) database and analyzed using limma. Protein-Protein Interaction (PPI) networks were constructed with STRING, and immune cell infiltration was analyzed using CIBERSORT. A risk model was built using LASSO regression. Drug screening was performed via CMap, and overexpression studies of CCND1 and HIF1A were conducted in AC16 and SEKHEP1 cells via cell proliferation, colony formation, and wound healing assays. Results We identified 182 common DEGs associated with HF. Hub genes CCND1, GABPA, HIF1A, and SOX6 were central in the PPI network. LASSO regression established a risk model linked to disease progression. Immune infiltration analysis revealed altered immune cell profiles in HF. The miRNA-mRNA network showed interactions of hsa-miR-93-5p, hsa-miR-802, hsa-miR-199a-5p, and hsa-miR-203a-3p with hub genes. Overexpression of CCND1 and HIF1A in cell lines impaired proliferation, colony formation, and migration, implicating their role in HF pathophysiology. Conclusion CCND1, GABPA, HIF1A, and SOX6 may serve as biomarkers for HF. Our findings provide valuable insights into immune infiltration, miRNA regulation, and the identification of therapeutic targets for HF management. These results highlight the role of gene regulation in HF progression and may guide future therapeutic interventions.